The Implementation of Religious Moderation Values in Islamic Education Learning at Cendekia Islamic Junior High School, Cianjur Regency, Indonesia - Dera Nugraha (LPPM IAIN Parepare, 2020)
Indonesia is the largest multicultural country in the world. Religious conflicts still occur today. The internalization of religious moderation values among its pluralistic society is the most strategic way to solve it. It needs to be started from early student education. Therefore, a study of the internalization of religious moderation values in basic education level is absolutely needed. This research was conducted at SMP Islam Cendekia Cianjur West Java, an islamic boarding school which has becoming one of Indonesia BRIDGE Schools since 2019. The method used is a case study with a qualitative approach. The results of this study indicate that the internalization of religious moderation values ​​in Islamic Education (PAI) learning is applied by the PAI teachers to all learning aspects; planning, implementing, and evaluation. In the planning aspect, they apply appreciation, responsibility, and simplicity values. They apply the values ​​of peace, happiness, and humble to the aspect of implementation. Then in the evaluation aspect the facilitators apply the values ​​of honesty, tolerance and cooperation. PAI teachers get policy support from the school management that was established in 2012.